ANALISIS KESALAHAN MAHASISWA DALAM MEMECAHKAN MASALAH MATEMATIKA BERDASARKAN ANALISIS NEWMAN DITINJAU DARI GENDER - Ririn Dwi Agustin (Program Studi Pendidikan Matematika, 2019)
Difficulties in learning are caused by student study programs in mathematics education to solve problems in solving mathematics. The mistake was made by both male and female students. In the course, algebraic structure is one of the material that requires the right procedure in its completion. This research includes descriptive analysis with qualitative data analysis. Data collection was carried out by test and interview methods conducted twice, namely TPM 1 and TPM 2. Subjects were considered as 2 students from 35 students of class 2016, consisting of one male student and one female student. The student has high mathematical skills. Each research subject was interviewed regarding the results of his work at TPM 1. To find the credibility of the data, the second test was conducted, which means that this study uses time triangulation. Furthermore, the data were analyzed to determine the types of student errors according to Newman's analysis. Based on the results of the study, data obtained that all research subjects did not make mistakes, errors, errors and answer errors. However, all research subjects made a mistake in the process at TPM 1 or at TPM 2. The male student subject made a mistake because he did not know the right way to use the existing formula. Meanwhile, female student subjects made mistakes because they did not understand the concept of exponents and chaos amid mathematical operations.